Positive Zeta Potential in Sandstones Saturated With Natural Saline Brine - Mutlaq Alarouj; Harry Collini; Matthew D. Jackson (Geophysical Research Letters)
Abstract It is widely accepted that the zeta potential in natural sandstones is negative in the brine pH and compositions found in the subsurface. The zeta potential is a measure of the electrical potential at a mineral surface. We report new measurements of the zeta potential using a saline natural brine rich in divalent ions. The sandstone samples were quartz dominated but some also contained dolomite, siderite, and clay minerals. The quartz‐dominated sandstones showed behavior consistent with earlier studies, but the dolomite‐ and siderite‐bearing samples returned positive zeta potentials. We suggest that this is caused by a positive zeta potential on dolomite and siderite mineral surfaces, adsorption of divalent ions onto quartz mineral surfaces, and/or ion exchange with clay minerals. The results have broad implications for the zeta potential of natural sandstones, because the magnitude and polarity of the zeta potential impact geophysical monitoring and the transport of the charged contaminants.